2015
DOI: 10.1111/agec.12170
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between gender, collective action for public goods and agriculture: evidence from Malawi

Abstract: Across the developing world, public goods exert significant impacts on the local rural economy in general and agricultural productivity and welfare outcomes in particular. Economic and social-cultural heterogeneity have, however, long been documented as detrimental to collective capacity to provide public goods. In particular, women are often underrepresented in local leadership and decision-making processes, as are young adults and minority ethnic groups. While democratic principles dictate that broad civic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Let us return to the substantive interpretation of our results. A long-standing finding concerning individual behavior in human societies is that homogeneity within a group facilitates collective action (Hardin 1982;Lichbach 1995;Alesina et al, 1999;Costa and Kahn, 2003b;Centola 2013;Kölle 2015;McCarthy and Kilic 2015;Baldassarri and Abascal, 2020;Mantilla et al, 2021;Drouvelis et al, 2021;Koch et al 2021). Our results indicate a potential additional pathway that may influence individuals to take action based on group identity.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 57%
“…Let us return to the substantive interpretation of our results. A long-standing finding concerning individual behavior in human societies is that homogeneity within a group facilitates collective action (Hardin 1982;Lichbach 1995;Alesina et al, 1999;Costa and Kahn, 2003b;Centola 2013;Kölle 2015;McCarthy and Kilic 2015;Baldassarri and Abascal, 2020;Mantilla et al, 2021;Drouvelis et al, 2021;Koch et al 2021). Our results indicate a potential additional pathway that may influence individuals to take action based on group identity.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 57%
“…An explanation of why the positive association between linking SCI and drought is not significant in areas most effected by drought requires further research to understand the findings. Previous research in Malawi found bridging social capital was positively associated with favourable growing conditions [111] and may explain why lower maximum temperatures are associated with a higher bridging SCI in the east coast and northern area of the Central Region. These areas have lower temperatures compared to the rest of the study area, so conditions are more favourable.…”
Section: Social Capital Typologies and Extreme Weather Eventsmentioning
confidence: 87%
“…Part of the problem is that rural environmental management is a type of regional public good (Mccarthy and Kilic, 2015) that involves a multitude of stakeholders as well as the distribution of benefits and responsibilities among them. In China, in the context of rapid urbanization and rural depopulation, the mechanisms for the maintenance of such village level public goods has collapsed leaving a situation where stakeholders fight for benefits as well as seeking to escape their responsibilities, leading to the failure of effective environmental management.…”
Section: Introductionmentioning
confidence: 99%